The Application of Circumstance Abuse Doctrine (Misbruik Van Omstandigheden) on Judicial Practice in Indonesia - HERNOKO, Agus Yudha; ANAND, Ghansam (Journal of Advanced Research in Law and Economics; Vol 8 No 7 (2017): JARLE Volume VIII Issue 7(29) Winter 2017, 2017)
This study analyzed the abuse of circumstances as a factor that delimits the freedom of making a contract associated with the onset of the contract, not because of the casue which is not allowed. The abuse of circumstance is not only related to the content of a contract, but rather related to what had happened at the time of the inception of the contract as one of the parties feels constrained to determine their will in a contract. It concerns on the circumstances that contribute to onset of the contract (i.e., taking benefit from other’s circumstance does not cause the content or intent of a contract be not permissible, rather, it may cause the missused will be restricted). The abuse of circumstances may happen due to one’s superiority over another party. The superiority is not only economic in nature, but also psychological, or both. Misusing such superiority may cause circumstance abuse. It is due to inequality of bargaining power that the weak cannot avoid from, while the stronger party abuses the circumstance by imposing the contents of the contract that leads to the inequal advantages for both parties. In Indonesia, the abuse of circumstances is often used as a cause to abrogate a contract due to the defect of will, although it is not yet regulated in legislation but rather derived from a legal construction recognized by the jurisprudence of the Supreme Court. It is definitely differenct from Netherlands that has regulated its misbruik van omstandigheden in article 3:44 lid 1 Nieuw Burgerlijk Wetboek .